Enhancing ESL Students’ Pronunciation Through Interactive Activities - Perez, Celso; Vergara, Sharon; Lezama, Verónica; Rivera, Eliphelet (CIEX JOURNAL, 2016)
This study aims to identify interactive activities that help improve pronunciation of ESL students of the Benemérita Universidad Autónoma de Puebla. The study explores this issue from the perspective of students and language teachers. In addition, the study provides information about the way teachers provide feedback regarding pronunciation errors and the strategies that they use to teach this important sub-skill. Results demonstrate that repeating, imitating, correcting errors, explaining mispronunciation, drilling through chain activities, using tongue twisters and reading aloud were some of the most frequent interactive activities perceived by both teachers and students to enhance English intelligible pronunciation.